How SARS-CoV-2 crisis could influence the tourism intentions of Azores Archipelago residents? A study based on the assessment of the public perceptions. (8th November 2022) - Couto, Gualter; Castanho, Rui Alexandre; Pimentel, Pedro; Carvalho, Célia Barreto; Sousa, Áurea
Tourism shows to be one of the most affected activities by the novel coronavirus SARS-CoV-2 (responsible for COVID-19) outbreak. This situation is not only because of the cancelled flights but also of the fear of being infected with the virus. In this regard, a study was carried out intending to define and analyse the consequences of SARS-CoV-2 over the tourism intentions of Azores residents in 2020 by studying their perceptions. Throughout the research, it was possible to verify that the Azores Archipelago residents' tourism intentions were considerably modified due to SARS-CoV-2, with approximately 70% of the Azores Region residents saying that they will be spending their 2020 vacations in the region. Moreover, this article also provides insights into the enhancement of tourism safety models in regional tourism activities and consequently, in regional sustainable development and growth.